Kekuatan Strategi Komunikasi Pemasaran terhadap Pesepsi Konsumen Kopi Sejuta Jiwa di Era Media Sosial - Nurpatria Kurniawan, Ergo; Joni Heruwanto (LPPM STEBIS YPII, 2026)
The Indonesian coffee industry is growing as the younger generation views coffee as part of their social lives. This trend has encouraged companies, such as Kopi Sejuta Jiwa, to use social media as a primary means of promoting their brands. This study examines how consumers perceive Kopi Sejuta Jiwa's social media marketing, specifically on Instagram and TikTok. The research used a qualitative descriptive method, focusing on students from Pelita Bangsa University who purchased the product and interacted with the brand's content. The results showed that consumers favored the company's strategy, particularly due to its consistent visuals, storytelling through mobile sales, friendly language, and quick responses. These efforts help build closer relationships with customers and increase their loyalty. However, several issues remain, such as unclear brand messaging and a lack of transparency regarding product details and halal certification. To improve these aspects, Kopi Sejuta Jiwa must strive to maintain consistent communication and provide clearer information to ensure greater marketing success in the coffee market.